10-Year changes in upper body strength and power in elite professional Rugby League players - The effect of training age, stage, and content - Baker, D. G. (The Journal of Strength and Conditioning Research, 2013)
The purpose of this investigation was to observe changes in maximal upper body strength and power across a 10-year period in professional athletes who were experienced resistance trainers. Six professional rugby league players were observed with test data reported according to 2 important training stages in their professional careers. The first stage (1996-1998) monitored the changes as the subjects strived to establish themselves as elite professionals in their sport. The remaining test data are from the latter stage (2000-2006), which is characterized by a longer competition schedule and shorter periods devoted to improving physical preparation. The changes in upper body strength, assessed by the 1 repetition maximum bench press and mean maximum power during bench press throws with various barbell resistances of 40-80 kg, were assessed by effect size (ES) and smallest worthwhile change (SWC) statistics. Large increases in strength and power of approximately 22-23% were reported across the 10-year period, however, only small changes (as determined by ES) in strength or power occurred after year 2000 till 2006. This result of only small changes in strength or power despite 6 years of intense resistance training was attributed to 3 main factors. Key among them are the possible existence of a "strength ceiling" for experienced resistance trainers, the Long-term Athlete Development model, and possibly an inappropriate volume of strength-endurance training from 2004 to 2005. The fact that an SWC in strength and power occurred in the year after the cessation of strength-endurance training suggests that training program manipulation is still an influencing factor in continuing strength and power gains in experienced resistance trainers.